2016
DOI: 10.1007/s10661-016-5185-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biosolids and compost amendment on chemistry of soils contaminated with copper from mining activities

Abstract: Several million metric tons of mining wastes, called stamp sands, were generated in the Upper Peninsula of Michigan during extensive copper (Cu) mining activities in the past. These materials, containing large amounts of Cu, were discharged into various offshoots of Lake Superior. Due to evidences of Cu toxicity on aquatic organisms, in due course, the materials were dredged and dumped on lake shores, thus converting these areas into vast, fallow lands. Erosion of these Cu-contaminated stamp sands back to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This was likely caused by the addition of soluble salts in the biosolids amendments. Sidhu et al (2016) found similar increases in EC from applying biosolids to copper mine tailings at application rates of 2.5%, 5%, 10%, and 20% of the dry weight, where maximum EC occurred in the 20% amendment rate. In contrast, biochar plots had the lowest EC values, which may be a result of adsorption of soluble salts on the charged surface.…”
Section: Discussion Soil Propertiesmentioning
confidence: 63%
See 1 more Smart Citation
“…This was likely caused by the addition of soluble salts in the biosolids amendments. Sidhu et al (2016) found similar increases in EC from applying biosolids to copper mine tailings at application rates of 2.5%, 5%, 10%, and 20% of the dry weight, where maximum EC occurred in the 20% amendment rate. In contrast, biochar plots had the lowest EC values, which may be a result of adsorption of soluble salts on the charged surface.…”
Section: Discussion Soil Propertiesmentioning
confidence: 63%
“…Unlike N, which is mobile in soils, P is less available, remaining in the soil through a wet season (Stevenson, 1986). In previous biosolid application studies, available P remained in the surface soil (0-10 cm; Maguire et al, 2000;Shober et al, 2003;Sidhu et al, 2016). In addition, Maguire et al (2000) found at 11 different test sites of varying application rates, iron and aluminum-bound P was the dominant form of P below 10 cm, which caused decreased plant available-P. Shober et al (2003) found no increase in available P below 10 cm after up to 18 years of annual biosolid application (53.71 Mg/ha).…”
Section: Nutrient Availabilitymentioning
confidence: 85%
“…The added benefit of using oilseed crops would be the production of biodiesel. In an earlier paper, we reported a lab incubation study, where we determined that the addition of compost to stamp sand improved its potential to support plant growth [8]. Our results showed that compost amendment resulted in a significant increase in the nitrogen (N), phosphorus (P), and organic matter (OM) content of stamp sand.…”
Section: Introductionmentioning
confidence: 82%
“…In the late 19th and early 20th centuries, the Upper Peninsula of Michigan was a major center for copper mining, generating millions of tons of mine tailings called stamp sands [4]. These metal-rich tailings were discharged into the shores of Lake Superior and other inland lakes in the region, severely impacting the aquatic ecosystem.…”
Section: Introductionmentioning
confidence: 99%